Linguistic Personological marker of Ordinary Political Discourse (on the example of Russian Internet comments) - Yergaliyeva, S.Z.; Melnik, N.V.; Yergaliyev, K.S. (KSU Publ., 2020)
The article is devoted to the results of a linguistic-personal research conducted on the basis of political Internet commentaries published on Russian sites. The article considers such aspects of the topic as: Internet communication, text-derivatology, linguistic-personology. In this study, special attention is paid to the virtual linguistic persona, reconstructed on the basis of their political Internet comments which manifest the linguistic abilities in the mental and psychological aspect. Methods of comparative-contrastive, descriptive methods and the method of quantitative estimation were applied in order to study this subject, and the research is based on the text-derivative analysis of derived texts, which are considered in the formal, content and functional plans. The purpose of the study is to determine the factors of personal text generation of Russian political Internet comments in the linguistic-personalological aspect. In the proposed article, a linguistic personality is reconstructed on the basis of political internet comments which reflect her linguistic abilities. In the course of linguistic analysis, the following methods were used: linguistic description, derivatological analysis technique, sampling method. As a result of analysis of political Internet comments, the parameters of the personal factor of text generation were revealed.
Қарапайым саяси дискурстың лингвоперсонологиялық маркері (ресейлік интернет-түсіндірме материалдары негізінде)
Лингвоперсонологический маркер обыденного политического дискурса (на примере российских интернет-комментариев)
Keywords: text derivatology; personal factors; ordinary political discourse; Internet comments; linguistic personality